Method development and clinical validation of LAMP-CRISPR/Cas12a for rapid detection of respiratory pathogens in children - Siyan Zhou; Xin Zhao; Fanzheng Meng; Fanzheng Meng (Frontiers in Pediatrics)
BackgroundRespiratory tract infections pose a substantial health burden, particularly among pediatric populations globally. The timely and accurate identification of pathogens such as Streptococcus pneumoniae (SP) and Mycoplasma pneumoniae (MP) is critical for effective clinical management.MethodsIn this study, a novel diagnostic approach combining loop-mediated isothermal amplification (LAMP) with CRISPR-Cas12a technology was developed for detecting SP and MP in clinical respiratory samples. A total of 23 specimens, including bronchoalveolar lavage fluid and nasopharyngeal swab samples, were assessed to evaluate the feasibility and performance of the method. After nucleic acid extraction, samples underwent LAMP amplification followed by CRISPR-Cas12a-mediated fluorescence detection.ResultsThe LAMP-CRISPR/Cas12a method demonstrated high sensitivity and specificity for SP detection. It exhibited excellent sensitivity for SP and promising specificity for MP. Comparative analysis with standard diagnostic methods highlighted its potential to enhance diagnostic accuracy and efficiency. The assay provided results within 1 h, which is suitable for rapid point-of-care testing.ConclusionThe integrated LAMP-CRISPR/Cas12a approach represents a significant advancement in detecting respiratory pathogens in clinical settings. It offers a rapid, sensitive, and specific diagnostic tool for identifying SP and MP, which is crucial for guiding precision therapies and improving patient outcomes. Future research aims to optimize assay sensitivity, streamline workflow to minimize contamination risks, and expand its detection scope so that other types of pathogens and mutation resistance genes can be detected. This molecular diagnostic strategy holds promise for the management of respiratory infections by enabling early and precise pathogen identification.